1988
DOI: 10.1113/jphysiol.1988.sp017200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha‐latrotoxin on the frog neuromuscular junction at low temperature.

Abstract: SUMMARY1. a-Latrotoxin (a-LTx) was applied to frog cutaneus pectoris muscles bathed at 1-3°C in either Ringer solution, Ca2"-free Ringer solution with 1 mM-EGTA and 4 mM-Mg2+ or Ringer solution plus 4 mM-Mg2+, and its effects on miniature end-plate potential (MEPP) frequency, nerve terminal ultrastructure and uptake of horseradish peroxidase (HRP) were studied.2. Large concentrations (2 ,ug/ml) of a-LTx increased MEPP rates to levels above 100/s at all junctions, but the time course of the increases depended u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…5). Furthermore, in agreement with immunofluorescence findings, a morphometric analysis carried out on electron micrographs of nerve terminals revealed that, in spite of the profound (-75%) depletion of SSVs (26), there was no significant change in the number of LDCVs (Table 1). …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…5). Furthermore, in agreement with immunofluorescence findings, a morphometric analysis carried out on electron micrographs of nerve terminals revealed that, in spite of the profound (-75%) depletion of SSVs (26), there was no significant change in the number of LDCVs (Table 1). …”
Section: Resultssupporting
confidence: 80%
“…The frog neuromuscular junction is the most thoroughly characterized model for the study of quantal release of classical neurotransmitters via SSVs (26)(27)(28). The detection of CGRP-containing LDCVs at these terminals opens the possibility of obtaining important new information on the relation between secretion of peptides and classical neurotransmitters from the same nerve ending.…”
Section: Discussionmentioning
confidence: 99%
“…The regulated, vesicular recruitment of AMPA receptors to the plasma membrane of growth cones was further supported by immunofluorescence experiments carried out in the presence of α‐latrotoxin, a potent stimulator of synaptic vesicle exocytosis (Ceccarelli et al ., 1988; Schiavo et al ., 2000; Sudhof, 2001). When applied to cultured hippocampal neurons in the absence of extracellular calcium, α‐latrotoxin not only induces synaptic vesicle exocytosis, but also prevents synaptic vesicle endocytosis (Pennuto et al ., 2002).…”
Section: Resultsmentioning
confidence: 82%
“…Miniature release can be regulated in a [Ca 2ϩ ] i -independent manner by agents that directly affect the presynaptic release machinery, e.g., ␣-latrotoxin (Ceccarelli et al, 1988;Capogna et al, 1996a,b) or ruthenium red (Trudeau et al, 1996). However, under physiological conditions, a strong [Ca 2ϩ ] i dependence of miniature synaptic activity is well documented (Matthews and Wickelgren, 1977;Marcus et al, 1992;Doze et al, 1995;Katz et al, 1995;Scanziani et al, 1995;Capogna et al, 1996aCapogna et al, , 1997Poisbeau et al, 1996;Schoppa and Westbrook, 1997;Bao et al, 1998;Li et al, 1998).…”
Section: Discussionmentioning
confidence: 99%